INTEGRATED SCHEME OF REGIONAL SUSTAINABLE DEVELOPMENT DRIVERS - Jazepčikas, Darius (Ekonomika, 2013)
Abstract. The complexity of sustainable development and the diversity of regions generate lots of challenges for the implementation of sustainable development at the regional level. In the process of implementation of the global sustainable development objectives, regions are taking different development paths because they are impacted by a unique internal interaction of the drivers. The problem is how the initial conditions of a region define the drivers and their interactions in the process of sustainable development policy implementation.The purpose of the study was to define a tool for the analysis of the interaction of drivers in the process of regional development moving towards sustainable development.The study methods were scientific literature analysis, conceptual, methodological, and visual modeling, and synthesis of the ideas.The paper concludes that an integrated scheme of drivers was used as an analytical method to explain how the difference in a region’s development level defines the path towards sustainable development. Synergy between the dimensions of a well-developed eco-centered region would be achieved by reforms in the economic and institutional dimensions. The scheme of a well-developed techno-centered region reveals a productive amalgamation among the institutional power, welfare level, and market mechanism. The scheme of a less-developedtechno-centered region reveals that reform actions are needed in all dimensions of sustainable development synchronically. Also, some extraordinary events or shocks have to happen to spur the reforms. The holistic view of the drivers suggests that a less-developed eco-centered region has to go the evolution path of social and environmental development, but with rapid reforms in both the institutional system and market relations.Key words: sustainable development, region, institutions, development dynamics